Math starters : 5- to 10-minute activities aligned with the common core math standards, grades 6-12 - Muschla, Judith A.; Muschla, Gary Robert; Muschla-Berry, Erin (San Francisco, CA : Jossey-Bass, 2013)
'A revised edition of the bestselling activities guide for math teachersNow updated with new math activities for computers and mobile devices--and now organized by the Common Core State Standards--this book includes more than 650 ready-to-use math starter activities that get kids quickly focused and working as soon as they enter the classroom. Ideally suited for any math curriculum, these high-interest problems spark involvement in the day's lesson, help students build skills, and allow teachers to handle daily management tasks without wasting valuable instructional time. A newly updated edition of a bestselling title Ideal for math teachers in grades six through twelve Includes more than 650 ready-to-use starter problems'--
Includes bibliographical references.
Keywords: Mathematics -- Study and teaching (Elementary); Mathematics -- Study and teaching (Secondary)